Lingo sorcery : the magic of lists, objects, and intelligent agents - Small, Peter (Wiley, 1999)
"Have you wanted to acquire that essential programming edge which will allow you to harness the full power of lists and objects? Are you looking to create innovative Director products for the Internet at the highest level of technical expertise? Have you reached that stage of using Lingo where the only next step you can take is to finally understand object-oriented programming?" "This second edition covers two major advances in Director which have opened up new vistas to users. Behaviors are easy to conceptualize, and allow those who have very little programming knowledge to design in an object-oriented programming (OOP) style. The new Application Programming Interface (API) introduced along with a set of Net Xtras has transformed Director from a closed application into an open system, allowing it to become the new killer app for the Internet and the Web."--BOOK JACKET.